Comparative assessment of SARS CoV2-associated mortalities in 3 COVID waves and related risk factors: The South Kashmir’s experience - Shujat Gul; Asifa Ali; Nawaz Ahmad Sheikh; Irfan Gul; Tariq Sultan Sheikh; Priyadarshi Prajjwal (Journal of Family Medicine and Primary Care)
Introduction: Severe acute respiratory syndrome coronavirus 2 causing coronavirus disease 2019 (COVID-19) pandemic have spurted in three major waves in India at different times and had different levels of severity in different waves. The objective of our study was to determine the comparative mortality rate in three COVID-19 waves and determine the factors associated with mortality. Methods: We identified a cohort of 1,132 COVID-19 patients who were admitted between April 14, 2020 and February 08, 2022 at our center. All the admitted patients with positive COVID–polymerase chain reaction were included in the study. Sample characteristics were determined by screening age, sex, socio-economic status, occupation, symptomatology of COVID, patient status on admission, baseline investigations, comorbidities, medical history, oxygen dosage needed during admission, the span of hospital stay, diagnosis, and vitals such as blood pressure, pulse, and oxygen saturation. All the data were procured from an institutional database. Results: In total, 1,132 patients included in the study, the mean age was 65.08 ± 12.29 and 56% were males. The affliction rate was 42.13% in >60 years, 29.5% in 46-60 years, 20.8% in 31-45 years, and 7.4% in 30 years’ group. In the first, second, and third waves of COVID-19, the mortality rates were 13.21%, 23.53%, and 11.39%, respectively. Among the comorbidities, mortality rates were proportionately higher in those with hypertension (6.7%), and diabetes (5.5%), than those with chronic obstructive pulmonary disease (3.3%), chronic kidney disease (CKD) (1.5%), heart disease (1.6%), and malignancy (0.2%). Conclusion: We identify the peaked mortalities in the second encounter which was predicted by age, comorbidities such as hypertension, and diabetes.